Guilty minds [compact disc, unabridged] : a novel - Finder, Joseph (Finder, Joseph. Nick Heller series, 2016)
The Chief Justice of The Supreme Court of The United States is about to be defamed, his career destroyed, by a powerful gossip website that specializes in dirt on celebrities and politicians. Their top reporter has written and exposé claiming that he had liaisons with an escort, a young woman prepared to tell the world her salacious tale. But the Chief justice is not without allies, and his greatest supporter is determined to stop the story in its tracks. Nick Heller is a private spy, an intelligence operative based in Boston, hired by lawyers, politicians, and even foreign governments. A high-powered investigator with a penchant for doing things his own way, he is called to Washington, D.C., to help out in this situation, delicate and potentially explosive. Nick has just forty-eight hours to disprove the story about the Chief Justice. But when the call girl is found murdered, the case takes a dangerous turn, and Nick resolves to find the mastermind behind the conspiracy before anyone else falls victim to the maelstrom of political scandal and ruined reputations predicated upon one secret, buried long.